2017
DOI: 10.2214/ajr.16.17195
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Ventilation-Perfusion Scintigraphy for Suspected Pulmonary Embolism

Abstract: Although advances in tomographic imaging have certainly improved the sensitivity of V/Q scans for the diagnosis of PE, they may lead to overdiagnosis by revealing small and clinically insignificant PEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Notably, the results from a pilot study by Soler, et al, also indicated that SPECT perfusion scanning was more sensitive than Planar V/Q for detecting segmental pulmonary artery obstructions in patients with CTEPH; however, the ventilation scans were conducted with 133 Xe gas and performed only in the planar mode, because SPECT ventilation was not available (18). In principle, this increased sensitivity may lead to unnecessary diagnoses and overtreatment of clinically insignificant defects in patients with acute PE (19), but this concern is less relevant in patients with CTEPH, for whom lifelong anticoagulant therapy is recommended. Perhaps more importantly, these observations suggest that V/Q-SPECT may be superior to Planar V/Q for identifying vessels that can be targeted during pulmonary endarterectomy and pulmonary balloon by on October 29, 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the results from a pilot study by Soler, et al, also indicated that SPECT perfusion scanning was more sensitive than Planar V/Q for detecting segmental pulmonary artery obstructions in patients with CTEPH; however, the ventilation scans were conducted with 133 Xe gas and performed only in the planar mode, because SPECT ventilation was not available (18). In principle, this increased sensitivity may lead to unnecessary diagnoses and overtreatment of clinically insignificant defects in patients with acute PE (19), but this concern is less relevant in patients with CTEPH, for whom lifelong anticoagulant therapy is recommended. Perhaps more importantly, these observations suggest that V/Q-SPECT may be superior to Planar V/Q for identifying vessels that can be targeted during pulmonary endarterectomy and pulmonary balloon by on October 29, 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Second, as in most studies of SSPE, the diagnosis of isolated SSPE was made by on-site radiologists and was not independently adjudicated [5,40,41]. Because the interobserver agreement for SSPE based on CTPA is only fair (k = 0.38) [8] and the diagnosis of SSPE based on ventilation/perfusion scanning is not standardized [42], we cannot exclude the possibility that some patients were misclassified as having isolated SSPE in our study. However, when we considered only CTPAbased PEs in a sensitivity analysis, the results did not change markedly, confirming the robustness of our findings.…”
Section: Tablementioning
confidence: 96%
“…This importance of a definitive end point in PH requires unequivocal lung scan interpretations. Recently, Stein et al (48) and Metter et al (49) studied lung scintigraphy for suspected acute pulmonary embolism in general patient populations and advocated for the replacement of probability-based V/Q lung scan interpretations with a more definitive approach, that is, normal, nondiagnostic or abnormal for PE. The same strategy 6 radiology.rsna.org n Radiology: Volume 00: Number 0-2021 highly suggestive of PAH with overt features of venous and capillary (PVOD/PCH) involvement (58,59) (Fig 2).…”
Section: V/q Scintigraphymentioning
confidence: 99%